Evaluation of phytotoxic potential and identification of phytotoxic compounds in Rumex maritimus. (4th July 2018) - Islam, M. S.; Iwasaki, A.; Suenaga, K.; Kato-Noguchi, H.
Abstract: Rumex maritimus (Polygonaceae) is an annual herb and is well known for its use in medicinal treatments. Although the pharmacological properties of R. maritimus are well documented, no phytotoxic activity of R. maritimus has yet been found. Therefore, we investigated the phytotoxic potential of R. maritimus to identify phytotoxic compounds. Inhibitory activity was found in aqueous methanol extracts of R. maritimus on the seedling growth of cress, rapeseed, barnyard grass, and foxtail fescue, in which inhibition increased with increasing extract concentration. Two compounds were isolated using chromatography, and using spectroscopy their structure was determined as 5, 7-dihydroxyphthalide and altechromone A. 5, 7-Dihydroxyphthalide significantly inhibited cress seedling growth by 27.2–43.0% of control seedlings at 3 mM, whereas altechromone A inhibited seedling growth by 65.4–66.3% at 0.01 mM. The concentrations required for 50% inhibition of cress seedling growth were 1.73–2.48 mM for 5, 7-dihydroxyphthalide and 0.66–1.41 mM for altechromone A. These results indicate that the compounds 5, 7-dihydroxyphthalide and altechromone A may contribute, to a certain extent, to the phytotoxic activity of R. maritimus .